1995
DOI: 10.1071/ar9950061
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of sorghum lines extracted from a population for differences in osmotic adjustment

Abstract: From 47 S2 lines which had been extracted from a random mated population of sorghum, eight lines for a glasshouse experiment and four lines for a field experiment were divergently selected for variation in osmotic adjustment, and were grouped into two, High and Low osmotic adjustment (OA). Both the glasshouse and field experiments examined whether osmotic adjustment modified the plants' response to soil water deficit and also whether grain sink demand for assimilates, varied by removal of 50% spikelets, affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Although the level of OA and the difference in wIL between the two poplar clones in our study were small, the fact that the TD clone had lower midday ww is consistent with other species that have the capacity for OA. Tangpremsri et al (1995) had reported that midday ww of sorghum decreased more in the high OA plants than the low OA plants, consistent with an earlier finding that genotypes with high OA or with low wx used more water than other genotypes (Tangpremsri et al 1991b). Morgan and Condon (1986) had also reported that water use of wheat genotypes with higher turgor maintenance was approximately 50% higher than genotypes with low turgor maintenance.…”
Section: Osmotic Adjustment and Growthsupporting
confidence: 82%
See 2 more Smart Citations
“…Although the level of OA and the difference in wIL between the two poplar clones in our study were small, the fact that the TD clone had lower midday ww is consistent with other species that have the capacity for OA. Tangpremsri et al (1995) had reported that midday ww of sorghum decreased more in the high OA plants than the low OA plants, consistent with an earlier finding that genotypes with high OA or with low wx used more water than other genotypes (Tangpremsri et al 1991b). Morgan and Condon (1986) had also reported that water use of wheat genotypes with higher turgor maintenance was approximately 50% higher than genotypes with low turgor maintenance.…”
Section: Osmotic Adjustment and Growthsupporting
confidence: 82%
“…For example, high OA lines of sorghum produced higher maximum leaf area at anthesis and maintained higher leaf area during grain filling under dry conditions (Tangpremsri et al 1995). Sorghum cultivars with high OA capability had slightly higher turgor than the low OA lines.…”
Section: Osmotic Adjustment and Growthmentioning
confidence: 95%
See 1 more Smart Citation
“…The increase of leaf proline at the intensity of drought stress in 25% field capacity of all varieties turned out to have a positive impact on the decreased weight of 1,000 grain of pithy rice at moisture content of 25% field capacity, especially in varieties that have high proline content such as Situ Patenggang and Towuti. Tangpremsi et al (1987) stated that there is no difference in seed yield between high and low osmoregulatory sorghum genotypes, but under conditions of high osmoregrative density, the genotype produced higher yields. The effect of osmoregulation on seed yield does occur because there is an improvement in the supply of assimilates from the leaf to the seed due to decreased leaf aging rate and improvement of photosynthetic activity of the leaves during drought.…”
Section: The Effect Of Drought Stress On the Measure Of Yield Componentmentioning
confidence: 99%
“…Although OA has been reported to be an important trait for drought tolerance in some cereal crops, e.g. wheat (Morgan et al, 1986) and sorghum (Tangpremsri et al, 1995), there are variable reports on the association of OA with grain yield in chickpea. Some studies have shown an association between OA and seed yield under water stress conditions (Morgan et al, 1991;Moinuddin and Khanna-Chopra, 2004), while some studies found inconsistent or no relationship (Singh et al, 1990;Leport et al, 1999).…”
Section: ) D E H Y D R a T I O N P O S T P O N E M E N T ( D Ro U G Hmentioning
confidence: 99%